2016
DOI: 10.5505/tjtes.2016.95525
|View full text |Cite
|
Sign up to set email alerts
|

War surgery in a Turkish hospital near the border of Syria: An evaluation in terms of critical and intensive care treatment principles

Abstract: The results of this study indicated that head-neck, chest-abdomen, and multiple body injuries are the most widely seen among civilians brought to Turkey because of gunshot injuries sustained during the Civil War in Syria. The number of emergency operations performed in the study sample was high, and critical care follow-up durations were long. In addition, the NISS and ASA scores of mortal cases were fairly high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Possibly due to its proximity to conflicts along the Syrian border, several studies highlighted the need for emergency care among Syrian refugees in Turkey when compared to other countries in the region. A study evaluating hospital admissions found the emergency department to be the most commonly used department [57], and gunshot wounds were found to be the most common cause of hospital admission [51], representing 84% [50] and 70% [5] of all admissions of Syrian refugees to the emergency department.…”
Section: Resultsmentioning
confidence: 99%
“…Possibly due to its proximity to conflicts along the Syrian border, several studies highlighted the need for emergency care among Syrian refugees in Turkey when compared to other countries in the region. A study evaluating hospital admissions found the emergency department to be the most commonly used department [57], and gunshot wounds were found to be the most common cause of hospital admission [51], representing 84% [50] and 70% [5] of all admissions of Syrian refugees to the emergency department.…”
Section: Resultsmentioning
confidence: 99%
“…However, the type of management of the PNI Table 4 Airway soft signs 2 × 2 contingency table. Table 5 Any soft signs 2 × 2 contingency table. shouldn't be determined by the mechanisms of assault or neck zone affected but by the signs and symptoms presented by the patient [3,4,11,18].…”
Section: Discussionmentioning
confidence: 99%
“…Penetrating neck injuries are more likely to occur in highly populated areas where there is more interpersonal violence and more gun and knife crime between young men [3]. Additionally, the rise of global terrorism and continuing wars in the Middle East has perpetuated head and neck injuries in the civilian population leading to elevated morbidity and mortality rates [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Although war surgery's spectrum is broad, surgeons have to deal with two main trauma mechanisms. Most of the injuries are caused by penetrating high velocity projectiles of any sort (BI and SI) or by blasts and burns from explosives like bombs or mines (SI and MI) [2].…”
Section: Pathway and Educationmentioning
confidence: 99%
“…Medical care in low-income countries (LIC) differs a from western medical standards [1]. Compared with civilian trauma in LIC, which is mainly caused by road traffic accidents, the injuries in war zones present different patterns with numerous wounds caused by bullets, mines, and bombs [2,3].…”
Section: Introductionmentioning
confidence: 99%